SISTEM PROTEKSI PETIR PADA GEDUNG UNTUK MEMINIMALISIR KERUGIAN DI SMKN 3 MATARAM - Ni Made Seniari; Supriyatna Supriyatna; Abdul Natsir; Ida Ayu Sri Adnyani; Sabar Nababan; I Made Ginarsa; Bagus Widhi Dharma S (Universitas Mataram, 2023)
Indonesia, being a tropical country, experiences more than 200 lightning strikes per year per square kilometer. The dangers associated with lightning currents cannot be completely eliminated. Therefore, it is crucial to make efforts to minimize losses caused by lightning strikes by installing both external and internal lightning protection systems. The impact of a lightning strike can cause harm to buildings, electronic equipment, and even pose a threat to the lives of living beings in and around the affected area. To safeguard buildings and protect lives from the dangers of lightning strikes, the installation of an external and internal lightning protection system is essential. In order to raise awareness about the importance of lightning protection systems, a socialization program was organized specifically for Vocational High School students majoring in building and electricity. This initiative is significant as Vocational High School graduates often enter the workforce directly. By integrating the concepts of building planning and electricity with lightning protection systems, it is hoped that Vocational High School students will begin to learn and apply these principles effectively. During the socialization program, the participants were familiarized with Law No. 28 of 2002 and Government Regulation No. 36 of 2005, which are both essential components of building planning. By incorporating these regulations into their understanding of lightning protection systems, the students gained valuable knowledge and skills. A total of 44 vocational students participated in this program, and their progress in terms of understanding and knowledge increased by 70.837%. This socialization activity holds great potential in minimizing losses caused by lightning strikes.